Persisting post-infection symptoms 2 years after a large waterborne outbreak of Cryptosporidium hominis in northern Sweden - Lilja, Mikael; Widerström, Micael; Lindh, Johan (BMC Research Notes, 2018)
Objectives: In 2010–2011, a large waterborne outbreak of Cryptosporidium hominis affected the city of Östersund in Sweden. Previous findings had suggested that gastrointestinal symptoms can persist for up to 11 months after the initial infection. Here we investigated whether the parasite could cause sequelae in infected individuals up to 28 months after the outbreak. We compared cases linked to the outbreak and the previous follow-up study with non-cases regarding symptoms present up to 28 months after the initial infection. We investigated whether cases were more likely to report a list of symptoms at follow-up compared to non-cases, calculating odds ratio and 95% confidence interval obtained through logistic regression. Results: A total of 559 individuals (215 cases) were included in the study. Forty-eight percent of the outbreak cases reported symptoms at follow-up. Compared to non-cases, cases were more likely to report watery diarrhea, diarrhea, abdominal pain, fatigue, nausea, headache, or joint stiffness/pain/discomfort at follow-up after adjusting for age and sex. Our findings suggest that gastrointestinal symptoms and joint pain can persist several years after the initial Cryptosporidium infection and should be regarded as a potential cause of unexplained gastrointestinal symptoms or joint pain in people who have had this infection.